NEW TYPES INDEX OF ACCOUNTING [ALL THAT CURRENTLY EXIST IN THE WORLD] - Valdivia Ramos, Román Arturo (2012)
In this research, it signals a new World Ranking types of accounting that currently exist in the world. We do not know a rating as extensive and detailed as the one presented, the product of a long academic research. This classification should be the foundation and / or support of further work to be carried or led by other researchers in the field. This is a rather unique classification, unlike anything known today. This is the contribution to the School of Accounting and makes the world accounting to the business world.